Christian Understandings of the Trinity : The Historical Trajectory - Kärkkäinen, Veli-Matti (Book collections on Project MUSE., 2017)
In this creative approach to the doctrine of the Trinity, author Veli-Matti Karkkainen focuses on keeping a dynamic balance between the intellectual-doctrinal and spiritual-charismatic approaches as parallel avenues towards theological understanding. His narrative approach draws on direct quotations from key historical theologians to increase appreciation of their theological wisdom and to encourage students to "dig further into this rich spiritual wellspring." The short, concise volumes in the Christian Understandings series orient and 'fill in the gaps' for readers as they dive into the exci.